The Many Faces of Covid-19 at a Glance: A University Hospital Multidisciplinary Account From Milan, Italy - Priori, Alberto; Baisi, Alessandro; Banderali, Giuseppe; Biglioli, Federico; Bulfamante, Gaetano; Canevini, Maria Paola; Cariati, Maurizio; Carugo, Stefano; Cattaneo, Marco; Cerri, Amilcare; Chiumello, Davide; Colosio, Claudio; et al. (Frontiers in Public Health, 2021)
In March 2020, northern Italy became the second country worldwide most affected by Covid-19 and the death toll overtook that in China. Hospital staff soon realized that Covid-19 was far more severe than expected from the few data available at that time. The Covid-19 pandemic forced hospitals to adjust to rapidly changing circumstances. We report our experience in a general teaching hospital in Milan, the capital of Lombardy, the most affected area in Italy. First, we briefly describe Lombardy’s regional Covid-19-related health organizational changes as well as general hospital reorganization. We also provide a multidisciplinary report of the main clinical, radiological and pathological Covid-19 findings we observed in our patients.